2018
DOI: 10.1111/ijfs.13940
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic compounds and thermal behaviour of African mango (Irvingia gabonensis (Aubry‐Lecomte ex. O'Rorke) Baill.) kernel fat

Abstract: Summary Irvingia gabonensis kernels are a promising oleiferous source. Their total lipid content was 72.3%. C14:0 and C12:0 represented the most abundant fatty acids. Triacylglycerols with ECN 32 and 46–48 were identified for the first time by HPLC‐DAD‐ESI‐MSn. Comprehensive GC‐FID and GC‐MS analyses revealed novel insights into minor lipids like phytosterols and tocochromanols. Among the latter, γ‐tocopherol was found to be the major vitamer. β‐Sitosterol and stigmasterol were the prevailing phytosterols in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…(2013) fractionated coconut oil and found that the high‐melting fraction of coconut oil had an increase about 7 °C of its maximum temperature from its pure coconut oil due to the increase in saturated fatty acids content as well as the rising content of SSS TAG type of components such as LaMM, LaMP, LaPP and LaLaM. RSF solid fractions were found to have higher T offset than of commercial CB (27.81–37.73 °C), MKF (30.53–36.02 °C), Illipe (38.0–39.4 °C) and POMF (36.86 °C) but lower than PS (51.4–56.13 °C) (Saadi et al ., 2010; Jahurul et al ., 2014, 2019a; Nazaruddin et al ., 2014; Bahari & Akoh, 2018; Lieb et al ., 2018). This indicated that RSF solid fractions are useful to be used as CBI either by blending with CB or other low‐melting fats to produce confectionery fats when high melting points are needed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2013) fractionated coconut oil and found that the high‐melting fraction of coconut oil had an increase about 7 °C of its maximum temperature from its pure coconut oil due to the increase in saturated fatty acids content as well as the rising content of SSS TAG type of components such as LaMM, LaMP, LaPP and LaLaM. RSF solid fractions were found to have higher T offset than of commercial CB (27.81–37.73 °C), MKF (30.53–36.02 °C), Illipe (38.0–39.4 °C) and POMF (36.86 °C) but lower than PS (51.4–56.13 °C) (Saadi et al ., 2010; Jahurul et al ., 2014, 2019a; Nazaruddin et al ., 2014; Bahari & Akoh, 2018; Lieb et al ., 2018). This indicated that RSF solid fractions are useful to be used as CBI either by blending with CB or other low‐melting fats to produce confectionery fats when high melting points are needed.…”
Section: Resultsmentioning
confidence: 99%
“…F 1 ‐S and F 2 ‐S started to crystallise at 28.7 and 29.33 °C which exhibited significantly ( P < 0.05) higher crystallisation temperatures than of crude RSF, and ended at 17.36 and 18.37 °C with enthalpy of 63.35 and 83.11 J g −1 (Table 3). The T onset and T offset of both solid fractions were found to be higher than of commercial CB (−5.20 to 17.71 °C and −26.2 to 5.59 °C) and CBEs such as MKF (16.08–18.52 °C), and POMF (17.64 °C) but lower than PS (28.4–32.73 °C) (Saadi et al ., 2010; Jahurul et al ., 2014, 2019a; Nazaruddin et al ., 2014; Lieb et al ., 2018). Moreover, the enthalpies of both solid fractions were also found to be higher than of commercial CB (56.98–58.0 J g −1 ) (Solís‐Fuentes & Duran‐de‐Bazua, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two clear issues that are addressed, namely the use analysis and potential use of compounds extracted from food raw material waste (e.g. mango kernels, Lieb et al ., , or red beet peels, Ralla et al ., ), and the utilisation of residual materials of plant origin (e.g. vegetables, Lafarga et al ., , or fruits, Quiles et al ., ) or of animal origin (Jayawardena et al ., ).…”
mentioning
confidence: 99%